Effect of bacterial inoculation on growth and yield of onion (Allium cepa L.) in Kilinochchi under greenhouse conditions - Shayanthan, A.; Gnanavelrajah, N.; Rajapaksha, R.M.C.P. (University of Ruhuna, 2019)
The search for microorganisms to improve soil fertility and crop production has continued to attract attention to offset the negative impacts of fertilizers in the environment in an ecofriendly way. The objectives of this study were to screen beneficial bacterial strains from onion (Allium cepa L.) rhizosphere from Thiruvaiyaru area in Kilinochchi district having the ability to fix nitrogen, solubilize phosphorus and/or produce indole-3-acetic acid and to select efficient strains in terms of onion productivity. Seven strains were screened for their N fixing and P-solubilization potential. The selected isolates together with previously screened three isolates were further evaluated for improving growth, and yield of onion in a pot experiment. The treatments were arranged in a completely randomized design with four replicates. The treatments were T1 (Non-fertilized), T2 (Rec NPK), T3 (Azo1), T4 (Azo3), T5 (Azo4), T6 (Azo5), T7 (Azo6), T8 (TSA1), T9 (TSA2), T10 (Azoj2), T11 (Azoj4), T12 (OD) and T13 (Cattle manure: CM). T2 (Rec NPK) was treated with recommended dose of CM (10t/ha) and NPK fertilizers; Urea (195kg/ha), Triple supper phosphate (100kg/ha) and Muriate of potash (75kg/ha). For the treatments T3 to T12 were treated with respective inoculum, CM (20t/ha) and Muriate of potash (75kg/ha). T13 was treated with CM (20t/ha) alone. All the inoculated plants showed significantly comparable height and number of leaves /plant with T2 (Rec NPK) throughout the growing season except T9 (TSA2). Significantly highest and lowest dry matter were produced in T7 (Azo6) and T9 (TSA2) respectively. The onion yield was increased by 24%, 25%, 20%, 20% and 31% in T3 (Azo1), T4 (Azo3), T6 (Azo5), T7 (Azo6) and T11 (Azoj4) respectively compared to T2 (Rec NPK). The correlation of co-efficient of yield and nitrogen uptake was 0.56 and yield and phosphorus was 0.65. Therefore, the inoculation of bacterial strains could exert positive impact on the growth, yield and nutrient uptake of onion. Among the bacterial strains Azo1, Azo3, Azo5, Azo6 and Azoj4 have the potential to increase onion growth and yield compared to others on growth and yield of onion.
Keywords: Onion; Screening; Bacterial strains; Yield